Time-spatial structure of airy pulse in non-stationary environment - Nerukh, Alexander; Kuryzheva, Olga; Benson, Trevor M. (2017)
A complex phenomenon including an asymmetric time varying Airy pulse and an asymmetric time varying bounded medium is considered. It is shown that this phenomenon is controlled by a generalised start parameter determined by the point of the source location and the moment of its initiation.